Implikasi Penetapan Bahasa Indonesia Sebagai Bahasa Internasional Terhadap Perkembangan Ekonomi Kreatif - Sulistiowati, Rini; Prahisa, Nurlela; Massayu, Novi; Zalianty, Nayla; anhar, Anhar (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the implications of Indonesian's status as an international language on the development of the creative economy in Indonesia. The method used is library research, reviewing various academic sources and policies related to language, the creative economy, and the language economy. The results of the study show that Indonesian plays a strategic role as a national identity and a medium for authentic cultural expression in creative products such as films, music, fashion, and digital content. The international status of the Indonesian language enhances the competitiveness and global market reach of creative industry players. Further analysis identifies three levels of strengthening strategies, namely the macro level through government policies that support language diplomacy and the creative industry, the meso level through the role of associations and creative communities in cross-cultural promotion, and the micro level through the innovation of creators who utilize a bilingual approach in their work. These findings show that Indonesian is not only a means of communication, but also a symbolic resource and cultural identity with high economic value. Thus, strengthening the position of Indonesian on the global stage can be a significant driver for national creative economic growth